Diseases of fruit crops - Gupta , V.K.; Satish K. Sharma (Chennai Kalyani, 2000)
it deals with the diseases caused by biotic factors such as fungi, bacteria, viruses , viroid phytoplasmas and nematodes
scab rust sooty mould base root soft root
Keywords: scab rust sooty mould base root soft root